Test of the multiquark structure of a1(1420) in strong two-body decays - Gutsche T. Thomas; Ivanov M. A. Mikhail; Korner J. G. Jurgen; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Xu Kai (2017, 2017)
Title screen